Kajian Tingkat Kerentanan Bencana Banjir di Kecamatan Baturaja Barat Kabupaten Ogan Komering Ulu Menggunakan Data Spasial dan Metode Overlay Berbasis Sistem Informasi Geografis - Luliana Luliana (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze the level of flood hazard in Baturaja Barat District, Ogan Komering Ulu Regency, by applying a spatial approach using Geographic Information Systems (GIS) through the overlay method. The analysis was carried out by integrating six main physical parameters, namely rainfall, land use, elevation, slope, river density, and soil type. Each parameter was assigned a score and weight according to its influence on flood potential and subsequently processed spatially to produce a flood hazard map. The results indicate that the Baturaja Barat District area is classified into three hazard levels: low (3.25%), moderate (70.64%), and high (25.84%). Areas with high hazard levels are predominantly characterized by densely populated settlements situated at low elevations and in close proximity to river networks, particularly in Tanjung Karang, Air Gading, Talang Jawa, Karang Agung, and surrounding villages. These findings highlight that land-use changes, topographic conditions, and the distribution of river networks play significant roles in increasing flood risk. The results of this study are expected to serve as a foundation for spatial planning, the strengthening of disaster mitigation policies, and the enhancement of community preparedness against flood hazards in the region.